Avenues to sustainable road transport energy in New Zealand. Issue 6 (2nd July 2016) - Kelly, Geoff
ABSTRACT: Reduction of the energy use and emissions associated with the provision of transport services is one of the most challenging areas of energy policy. This arises both from the pervasive nature of transport use in modern society and its dependence on the most limited of fossil fuels. Advances in renewable energy utilization offer an avenue by which this may be addressed, including the possibility of achieving fully sustainable transport energy supply. The article considers what potential exists for sustainable road transport energy in New Zealand. That country already has high renewable energy utilization, but also a high per-capita transport demand and limited domestic hydrocarbon resources. Three main routes for renewable fuel supplies are examined, with the conclusion that two (the production of biofuels from forest products, and the amplification of electricity supply from renewable energy sources for use in electric vehicles) offer technically feasible pathways toward a fully sustainable transport energy system. Cost and confidence in investment remain the principal barriers to this development.